PENGETAHUAN PAJAK, PENERAPAN E-SAMSAT, DAN KONDISI KEUANGAN WAJIB PAJAK TERHADAP KOMITMEN PATUH WAJIB PAJAK KENDARAAN BERMOTOR - Frediansyah, Frediansyah; Kurniawati, Lintang (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to examine whether there is an influence of auditor independence, due professional care, audit fees and audit tenure on audit quality. The population in this study were auditors who worked at KAP in East Jakarta. The number of samples in this study were 67 respondents. The sampling technique uses purposive sampling method. The research method used is quantitative with primary data sources. The methode of data analysis uses multiple linear regression analysis with SPSS version 25. The results of this study provide empirical evidence that partially auditor independence variables, due professional care, audit fees and audit tenure in a positive direction have a significant effect on audit quality. Simultaneously the auditor independence variables, due professional care, audit fees and audit tenure with a positive direction have a significant effect on audit quality.